C–C coupling at a zeolite-supported Rh(i) complex. DFT search for the mechanism. Issue 11 (15th May 2019) - Vummaleti, Sai V. C.; Kuriakose, Nishamol; Dinda, Shrabani; Wu, Yin; Genest, Alexander; Rösch, Notker
Abstract : DFT modelling suggests a metallacycle mechanism for the dimerization of ethene over a faujasite-supported Rh(i ) complex, rationalizing the experimental selectivity. Abstract : The faujasite-supported Rh(i ) complex [Rh(C2 H4 )2 ] + was suggested as the active species in experiments showing the catalytic dimerization of ethene to butene in a highly selective fashion (78%), with ethane as side product (19%). As previous theoretical work determined only ethane formation for the reported complex, the present computational work set out to identify a potential mechanism, a migratory insertion (Cossee–Arlman) or metallacycle type, employing a quantum mechanics/molecular mechanics (QM/MM) procedure. Our results exclude the bifunctional mechanism suggested by the experimentalists because we estimated pertinent C–C coupling activation barriers above 125 kJ mol −1 . Next we turned to modelling more complex scenarios involving three ethene ligands at the metal center, [Rh(C2 H4 )3 ] + . For such an active complex, we determined the in situ generated diethyl intermediate [Rh(C2 H4 )(C2 H5 )2 ] + as a branching point, yet found ethene hydrogenation favorable over dimerization via a Cossee–Arlman mechanism, with free activation energies of 55 kJ mol −1 and 103 kJ mol −1, respectively. Finally, we addressed a metallacycle mechanism for the dimerization of ethene that allows one to rationalize the experimental selectivity for butene. The crucial relative free energy barrier of the C–C coupling step is calculated at 68 kJ mol – 1 . The latter barrier is lower by 6 kJ mol −1 in absolute terms than the hydrogen activation for the Cossee–Arlman mechanism, rendering the metallacycle mechanism the most preferred pathway. To arrive at a conclusive understanding of this chemistry, the present work serves to build a bridge to experimental research by addressing pertinent observations.